Changes in soil organic matter content and quality after application of different organic and mineral fertilisers in 27 years long-term field experiments on luvisol - Balík, Jiří; Suran, Pavel; Černý, Jindřich; Sedlář, Ondřej; Kulhánek, Martin; Procházková, Simona (Frontiers in Soil Science, 2025)
The soil organic matter (SOM) content and quality are the fundamentals of soil fertility and contribute significantly to soil carbon sequestration. The soil glomalin content is increasingly recognized as an indicator of SOM quality. The objective of this study was to evaluate the capability and contribution of the easily extractable glomalin (EEG), total glomalin (TG) content, potential wettability index (PWI) of soil aggregates, and water stability of soil aggregates (WSA) as instrumental indicators of long-term SOM quality changes. The obtained results on EEG, TG, PWI, and WSA were compared to the results of humic substances fractionation, specifically their relationship to carbon in humic substances, humic acids, and fulvic acids (CHS, CHA, and CFA, respectively). We used long-term field experiments (27 years) with a simple crop rotation starting with potatoes (site A) or maize (site B), followed by winter wheat and spring barley (on both sites) on the luvisol soil type. Fertiliser treatments were based on the application of uniform 330 kg N ha-1 per three years. Treatments were as follows: unfertilised control (Cont), sewage sludge in normal and triple dose (SS1 and SS3, respectively), farmyard manure in the conventional dose and half dose with mineral nitrogen (F1 and F1/2+N1/2, respectively), straw and mineral N fertiliser (N+St), and mineral N only (N). For the evaluation of the fertiliser effect, data from both sites were pooled together. The farmyard manure application in the F1 treatment showed the best potential for improving the SOM quality (the highest CHA, humification rate, humification index, TG content, and WSA). The results of Cont treatment show degradation of SOM content and quality. No significant effect of fertiliser treatment on the EEG was observed. The TG content was significantly influenced by fertiliser in the F1, F1/2+N1/2, and SS3 treatments (1965, 1958, and 1989 mg kg-1, respectively) in comparison with the Cont (1443 mg kg-1). The TG content was in a tight relationship with the CHA content (R2 = 0.298; p<0.001). The PWI was also influenced by the treatment. There was a significant positive relationship between PWI and CHS (R2 = 0.550), CHA (R2 = 0.249), and CFA (R2 = 0.492), p<0.001. No significant relationship was established between the WSA and SOM quality indicators. Both TG content and PWI can be used as indicators of SOM quality in long-term experiments. On the other hand, the EEG content and WSA are not capable of determining the changes in the SOM quality.